2020
DOI: 10.1371/journal.pone.0234088
|View full text |Cite
|
Sign up to set email alerts
|

Marker Assisted Gene Pyramiding (MAGP) for bacterial blight and blast resistance into mega rice variety “Tellahamsa”

Abstract: Bacterial blight (BB) and fungal blast diseases are the major biotic constraints that limit rice productivity. To sustain yield improvement in rice, it is necessary to developed yield potential of the rice varieties by incorporation of biotic stress resistance genes. Tellahamsa is a welladapted popular high yielding rice variety in Telangana state, India. However, the variety is highly susceptible to BB and blast. In this study, simultaneous stepwise transfer of genes through marker-assisted backcross breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 39 publications
(54 reference statements)
1
20
0
2
Order By: Relevance
“…RPG recovery in the two crosses in the present study did not differ from several earlier wheat breeding programmes where MABB was used for introgression of genes/QTL for biotic and abiotic stresses in wheat (Yadav et al 2015;Mallick et al 2015;Vishwakarma et al 2016;Rai et al 2018;Randhawa et al 2019;Todkar et al 2020: Gautam et al 2020a). This con rmed the utility of MABB for effective introgression of genes/QTL into the agronomically superior genotypes associated with recovery of recurrent parent genome in a relatively short time as also reported earlier in wheat (Mallick et al 2015), rice (Divya et al 2015;Ellur et al 2016;Ramalingam et al 2020;Jamaloddin et al 2020), and maize (Sureshkumar et al 2014;Kaur R et al 2020).…”
Section: Resultssupporting
confidence: 82%
“…RPG recovery in the two crosses in the present study did not differ from several earlier wheat breeding programmes where MABB was used for introgression of genes/QTL for biotic and abiotic stresses in wheat (Yadav et al 2015;Mallick et al 2015;Vishwakarma et al 2016;Rai et al 2018;Randhawa et al 2019;Todkar et al 2020: Gautam et al 2020a). This con rmed the utility of MABB for effective introgression of genes/QTL into the agronomically superior genotypes associated with recovery of recurrent parent genome in a relatively short time as also reported earlier in wheat (Mallick et al 2015), rice (Divya et al 2015;Ellur et al 2016;Ramalingam et al 2020;Jamaloddin et al 2020), and maize (Sureshkumar et al 2014;Kaur R et al 2020).…”
Section: Resultssupporting
confidence: 82%
“…For example, in a recent study, gene pyramided lines were evaluated for key agro-morphological traits, quality, and resistance against blast at different hotspot locations. Two ICF 3 genes, pyramided lines viz., TH-625-159, and TH-625-491 possessing Pi54 and Pi1 genes, exhibited a high level of resistance to blast [195]. Often gene pyramiding, ably supported by MAS, involves assembling more than one gene for different insect pests or diseases or a combination of both.…”
Section: Gene Pyramidingmentioning
confidence: 99%
“…Marker-assisted gene pyramiding of resistance QTLs have been successfully applied in several crops consequently producing a number of varieties and lines with improved resistances against biotic stresses, such as late blight, bacterial blight, gall midge, mosaic viruses, powdery mildew and many abiotic stresses, such as salinity, drought, heat, and cold with a higher yield and desired nutritional quality (reviewed by Dormatey et al, 2020 ). Especially, the multi-loci polymerization resistance breeding is a success story in rice where plant scientists successfully utilized this technique to accomplish durable resistance against various diseases such as gall midge ( Das and Rao, 2015 ), blast ( Jamaloddin et al, 2020 ), brown planthopper ( Liu et al, 2016 ), bacterial blight ( Singh et al, 2001 ; Joseph et al, 2004 ; Jamaloddin et al, 2020 ; Ramalingam et al, 2020 ), sheath blight ( Ramalingam et al, 2020 ), blast and bacterial blight ( Narayanan et al, 2002 ), bacterial, sheath blight and stem borer ( Datta et al, 2002 ) etc. Wu et al (2019) identified 37 SNP polymerization regions for 36 agronomic traits in 287 pepper accessions which could be the focus of molecular marker development to improve the efficiency of multi-trait pyramid breeding.…”
Section: Downy Mildewmentioning
confidence: 99%